A expertise na coprodução de serviços intensivos em conhecimento: uma análise em relações entre empresas - Rabêlo, Josélia Maria de Oliveira (2017)
The objective of this research was to analyze how customers and suppliers create value by exchanging expertise in B2B relations, in knowledge intensive services. To better understand the relationship of these variables, an exploratory research strategy was adopted, because it allows analyzing the phenomenon through different perspectives - clients, suppliers and interaction between them. Field research was conducted in two phases. Phase 1 was used to deepen understanding about the topic of interest in diverse contexts. Nine interviews were conducted with managers of different types of knowledge intensive services – Human Resource Consultancy, Software and Engineering and Architecture. The results showed that complexity, customization and strategic relevance of the solution motivates the customer to participate in the co-production. The results of co-production are optimized when customers and suppliers interact and share their expertise throughout the phases of diagnosis and execution of the solution. Interaction between customer and supplier, and technical and business expertise sharing positively influence the client's perception of value. Customer participation in the co-production has positive effects on both economic and relationship value. Finally, it was observed that customers perceive the solution broadly including functional and also relational benefits of the solution. Phase 2 of the research was aimed at companies belonging to the architecture segment. It was adopted, as a research strategy, the study of multiple cases. Five cases of interaction between company and its client were conducted. Twenty semi-structured interviews were carried out, eight managers of the supplier companies and 12 client managers of these companies. In addition, secondary data on the participating companies were collected and field notes were taken. The results showed that the way in which customers and suppliers combine and complement business and technical expertise influences the coproduced results and the perceived value of the offer.This second phase has also revealed that coproduction is most effective when customers are more experienced, have business expertise, communicate their expectations and share this business expertise with their suppliers. The results suggest that the perception of economic value creation is more present when services are more complex, especially when the solution requires technical expertise exchange between clients and suppliers. The perception of economic and relationship value is more present when the solution requires technical and business expertise complementarity between clients and suppliers. The results also showed that expertise exchange between clients and suppliers depend on boundary spanners skills and capacities on both to achieve better results in service production. Some boundary spanners skills and capacities favor coproduction: encouraging the interaction of the external contact agent with the company and stakeholders, frequency of contact during the coproduction, engagement and motivation to participate in the solution, communication, flexibility, acceptance of suggestions and comments and negotiation.